Understanding the effects of social media use on construction project performance: a project manager's perspective - Ma, Guofeng; Jiang, Shan; Wang, Ding (Engineering, construction, and architectural management, 2022)
PurposeAlthough social media has been increasingly applied and valued in the construction industry, there has been little evidence revealing the influence mechanism of social media use in the construction context. In this way, this paper aims to explore how different purposes of social media use affect project performance from a project manager's perspective.Design/methodology/approachDrawing on the mechanism–outcome–performance framework, this paper developed a research model to figure out the mechanism through which work-oriented and socialization-oriented social media use influences construction project performance. The empirical data were collected from a survey of 249 construction project managers, and the structural equation modeling technique was applied to test the proposed model.FindingsResults indicate that both work-oriented and socialization-oriented social media use promote knowledge acquisition and project social capital, which both further positively impact the project performance. Additionally, the negative moderating role of information overload is identified on the relationship between social media use and knowledge acquisition.Originality/valueThis study fulfills the need for an in-depth investigation of social media use on construction project performance, contributing to the project management and social media literature. Furthermore, this study provides recommendations for project managers to advance social media applications in the construction domain.